2013
DOI: 10.1155/2013/342869
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Brachial-Ankle Pulse Wave Velocity in Chinese Patients with Rheumatoid Arthritis

Abstract: Objective. To investigate the relationship between Brachial-ankle pulse wave velocity (baPWV), and its associated risk factors in Chinese patients with RA. Methods. 138 Chinese RA patients and 150 healthy subjects were included. baPWV of all the participants was measured. RA related factors were determined, as well as traditional cardiovascular risk factors. Results. baPWV was significant higher in RA group (1705.44 ± 429.20 cm/s) compared to the healthy control group (1386.23 ± 411.09 cm/s) (P < 0.001). Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
1
3
0
1
Order By: Relevance
“…We are not aware of studies who examined the relationship between ANA and cfPWV. Finally, our findings regarding the missing association between aortic stiffness and RA disease duration are in agreement with other RA/cfPWV studies (Mäki-Petäjä et al 2006 ; Provan et al 2011 ; Li et al 2013 ).…”
Section: Discussionsupporting
confidence: 93%
“…We are not aware of studies who examined the relationship between ANA and cfPWV. Finally, our findings regarding the missing association between aortic stiffness and RA disease duration are in agreement with other RA/cfPWV studies (Mäki-Petäjä et al 2006 ; Provan et al 2011 ; Li et al 2013 ).…”
Section: Discussionsupporting
confidence: 93%
“…In other studies, repeatability of AIx were examined, where intra-observer ICC ranged from 0.75 to 0.96 [47] [49] and inter-observer ICC ranged from 0.92 to 0.93 [47] ; Intra-observer ICC of PWV ranged from 0.75 to 0.92 [50] [52] and inter-observer ICC of PWV was 0.88 [53] ; The intra-observer ICC of central systolic blood pressure reconstruct from transfer function was 0.74 in resting state [48] . Comparing to other index of PWA, the harmonic components are competitive and reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Higher arterial stiffness correlated with elevated nighttime SBP and the non-dipping pattern [ 21 ]. In addition, higher levels of triglycerides, total cholesterol, low-density lipoprotein (LDL), glucose, and increased body mass index (BMI) were seen in our discussed population [ 3 , 5 , 6 , 13 , 22 , 23 , 24 ]. Many studies ruled out smokers from study groups because of the evident vasoconstrictor effect, and only some studies showed a higher prevalence of smokers [ 5 , 6 ].…”
Section: Reviewmentioning
confidence: 92%
“…Prevalence does not necessarily mean causation. High SBP, DBP, total serum cholesterol, LDL, BMI, insulin resistance, and smoking are related to vascular morphological characteristics, measured by pulse wave velocity (PWV), augmentation index (Aix), and ankle-brachial Index (ABI) [ 5 , 6 , 18 - 20 , 23 , 25 ]. ED is associated with SBP, LDL, smoking, and age [ 2 , 24 , 28 ].…”
Section: Reviewmentioning
confidence: 99%